Title Of The Article : Methodologie Of Educational Handwriting Control In The Quran Schools During The French Colonial Period In Tidikilt Region –sidi El Hadj Mohammed Abdelkader Elbarmaki As A Model - Ben Abou, Mohamed (El Omda in Linguistics and Discourse Analysis, 2024)
Tidikilt region is a region That is deeply rooted in history. Its scholars have made great efforts to preserve The Arabic lqnguage Through mosques Quran schools and in some Zawaya Where Those scholars were Keen to indoctrinate The young generation The Holy Quran Throught memorizing it and writing it . In addition To juristic and linguistic principles and that is throught coping it from books to hearts and Vice Verses. –Sidi El hadj Mohammed Abdelkader Elbarmaki one of them.